Factors Affecting the Adoption of Forage Technologies under Smallholder Dairy Production Systems in Tanzania - Ndah, Hycenth T.; Schuler, Johannes; Paul, Birthe K.; Nzogela, Beatus; Mangesho, Walter E.; Mollel, Richard; Loina, Rose; Kengwa, Venance (International Center for Tropical Agriculture, 2017)
70% of the world’s bovines belongs to LDCs, but they only produce 29% of the global meat and 23% of the global milk output (Jahnke et al. 1988). Current demand for dairy products in Africa largely outweigh their production (Smith 2015; Lukuyu et al. 2009). A comparative study showed a 4.0% demand growth rate against a 3.1% production growth rate of dairy products in SSA between 1990 and 2004 (Ndambi et al. 2007),